APPEARANCE OF NEUTROPHIL-LYMPHOCYTE RATIO ON YOUNG ADULTS AFTER FUTSAL SPORT IN THE NIGHT - Arwan Bin Laeto; La Jumadin; Haslinda DS (Majalah Kedokteran Sriwijaya, 2021)
Exercise is the easy and cheapest effort that can be did to maintain health level and increase the immune system. The dense activity during the day makes people doing exercise at the night. Neutrophil-lymphocyte ratio (NLR) is a one of indicator that can be use to evaluate the inflammation process caused by exercise. This study aims to determine the appearance of neutrophil-lymphocyte ratio on young adult after futsal sport in the night. This research was a quasi experimental with the subjects were 10 young adults for intervention and control respectively that satisfy the inclusion criteria. Measurement of total leukocyte, count type of leukocyte and neutrophil-lymphocyte ratio were conducted before and after 2 x 20-minute futsal sport in the night. The data form each group were analysed statistically using the pair t-test. The results showed that there was significant change in the all indicators to intervention group, namely total leukocyte p = 0,01 (p<0,05), neutrophil p = 0,01 (p<0,05), lymphocyte p = 0,01 (p<0,05), and NLR p = 0,01 (p<0,05). The conclusion proved that exercise at the night can cause significant changes of neutrophil-lymphocyte ratio on young adult.